STEM-Focused Activities to Support Student Learning in Primary School Science - Neslihan Ultay; Arzu Zıvalı; Hilal Yılmaz; Hilal Konçuy Bak; Kezban Yılmaz; Melek Topatan; Pelin Gül Kara (Journal of Science Learning, 2020)
This study examines the effect on student academic success through teaching the "Let's Know the Matter" grade 3 science unit accompanied by STEM (Science, Technology, Engineering, and Mathematics)-focused activities. The study group consisted of 24 third grade students studying in the 2019-2020 academic year. Teaching was done with a 5E (enter, explore, explain, elaborate, evaluate) instructional model, and student opinions about the STEM activities were collected. A group pretest-posttest research design was used in which the "Let's Know the Matter Test (MT)" was administered at the beginning to measure the students' prior knowledge, and again at the end of the unit to determine what students had learned. Their opinions of the lessons taught with STEM-focused activities were collected using a semi-structured interview technique. Qualitative data were divided into appropriate categories under common themes. It was observed that the 5E instructional model contributed to their academic success. Also, it was found that their opinions about the lessons taught with STEM activities were quite positive. Based on the results obtained from the research, it is suggested that STEM activities be used in the teaching of other topics.